George Reginald Balleine: Historian of Anglican Evangelicalism. Issue 1 (7th October 2013) - Atherstone, Andrew
Abstract A History of the Evangelical Party in the Church of England (1908) by G.R. Balleine (1873–1966) is the classic narrative history of the Anglican evangelical movement, still enduringly popular more than a century after its publication. It has long outlived its author but is usually read without reference to him. This paper examines Balleine's approach to historical research and demonstrates how his personal theological priorities shaped his History. In particular, it highlights his concerns in his parish ministry in Bermondsey, south London, for innovative evangelism, political activism and loyal Anglican churchmanship; his disinterest in doctrinal definitions and his abhorrence of ecclesiastical controversy. The paper argues that Balleine's lively account of Anglican evangelicalism's past in the eighteenth and nineteenth centuries was also an apologia and mandate for the future direction of the movement as it entered the twentieth century. It concludes by pointing to the sharp irony that while the History has gained a reputation for impeccable evangelical credentials, the historian was on a divergent trajectory away from his evangelical roots.